FACTORS INFLUENCING TASK MANAGEMENT SKILLS AMONG SOCIAL WORK STUDENTS AT MALAYSIAN PUBLIC UNIVERSITIES - Kamarudin, Nazihah (International Journal of Psychosocial Rehabilitation, 2020)
Task management is an important skill needed by social work students in preparation for becoming professional social workers. Therefore, this article aims to measure the level of task management skills and factors influencing the aspect of task management among social work students atMalaysian public universities. This study applies quantitative research design by cross-sectional survey. A total of 215 final year social work students from six public universities in Malaysia were selected as respondents of the study. The study data was analysedusing descriptive and inference statistics. Based on the results, social work students at public universities have moderate to high levels of task management skills. This study also found that the variables of leadership ability, problem solving ability and ethical behaviour are major predicting factors that can influence task management skills among final year social work students at public universities.The findings of this study have positive implications to the university management especially to the benefits ofsocial work programs at public universities. The existing curriculum can be improved to enhance the social work students’ skills in managing their tasks and in preparation for becoming professional social workers.